Indonesia's Efforts in Resolving South China Sea Conflict - Aprilla, Wines (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2023)
This research tries to explain Indonesia’s effort in the South China Sea conflict resolution process. The South China Sea conflict can lead to regional instability. Indonesia can’t directly resolve the conflict because Indonesia is not a claimaint state. But, Indonesia can encourage claimant states to resolve their conflicts peacefully. As the largest country in ASEAN, Indonesia has an obligation to maintain the stability of the region. The type of this research is descriptive qualitative with data collection technique through interview and literature study. The results concluded that Indonesia's efforts in establishing the situation through confidence buiding measures and cooperation has been able to dampen the source of conflict and keep the region stable. Indonesia has managed conflict even though it is still very far from the possibility of conflict resolution.